AGMEMOD outlook for agricultural and food markets in EU member states 2018-2030 - Petra Salamon; Martin Banse; Trevor Donnellan; Marlen Haß; Roelof A. Jongeneel; Verena Laquai; Myrna van Leeuwen; Ioanna Reziti; Guna Salputra; Max-Emanuel Zirngibl (Johann Heinrich von Thünen-Institut, 2019)
Policy, administration and industry need medium-term projections of the expected developments in the agri-food markets for their decision-making processes. The EU Commission presents such projections for the EU as a whole in December of each year. Those projections and their assumptions regarding policy and macroeconomic developments are depicted to the level of individual EU Member States with the exception of Luxembourg, which is included in the figures of Belgium, by applying the partial equilibrium model AGMEMOD. The working paper briefly describes the approach to establish projections for the EU Member States. The projections cover the markets of main agricultural products, in particular for cereals and oilseeds (rapeseed and sunflower seed), livestock (cattle, pigs, goats and sheep), meat (beef, pork, and poultry), milk and dairy products (drinking milk, butter, cheese, skimmed milk powder, whole milk and semi-skimmed milk powder). The outcomes comprise items like areas, livestock numbers, yields, production, trade and use, as well as prices. The individual projection results are displayed in tables. – – Politik, Administration und Wirtschaft benötigen für ihre Entscheidungen mittelfristige Projektionen über die zu erwartenden Entwicklungen auf den Märkten der Agrar- und Ernährungswirtschaft. Die EU-Kommission legt solche Projektionen für die EU als Ganzes im Dezember jedes Jahres vor. Diese Projektionen und ihre Annahmen bezüglich politischer Maßnahmen und makroökonomischer Entwicklungen werden mit Hilfe des partiellen Modellsystems AGMEMOD auf die einzelnen EU-Mitgliedsstaaten mit der Ausnahme von Luxemburg, das mit Belgien regional zusammengefasst wird, herunter gebrochen. Das Working Paper beschreibt kurz den Ansatz, wie die Projektionen für die Mitgliedsstaaten erstellt werden. Die Projektionen umfassen die Märkte für wichtige Agrarprodukte, und zwar insbesondere für Getreide und Ölsaaten (Raps- und Sonnenblumensaat), für Vieh (Rinder, Schweine, Ziegen und Schafe), Fleisch (Rind-, Schweine- und Geflügelfleisch), Milch und Milchprodukte (Trinkmilch, Butter, Käse, Magermilchpulver, Vollmilch und teilentrahmtes Milchpulver) und decken Anbauflächen, Tierbestände, Produktion, Handel und Verwendung sowie Preise ab. Die einzelnen Projektionsergebnisse werden in tabellarischer Form aufbereitet dargestellt.
urn:nbn:de:gbv:253-201812-dn060597-2
Keywords: C30; Q11; Q13; 630; projections; agricultural market; PE; agricultural market model; dairy market; meat market; grain market; oilseed market; EU member states; Projektionen; Agrarmarkt; Agrarmarktmodell; Milchmarkt; Fleischmarkt; Getreidemarkt; Ölsaatenmarkt; EU-Mitgliedsstaaten